Long‐term observation of waterfowl migration in the south‐east of the forest zone of Western Siberia, Russia - I. G. Korobitsyn; O. Yu. Tyutenkov; A. S. Panin; E. B. Murzakhanov; A. V. Bazdyrev (Юг России: экология, развитие, 2024)
The aim of this research is an analysis of the long‐term dynamics of the composition and number of migratory waterfowl in the southeast of the forest zone of Western Siberia.Visual observations of waterfowl migration were carried out in the format of daily 2‐hour morning counts in April‐May through a period 18 years (1998–2023) near the Tomsk on the Tom river. Additionally, in 2002–2003, simultaneous migration was also observed on the Ob river in the southern, central and northern parts of the Tomsk region. The method of E.I. Gavrilova and E.V. Kumari was used with some modifications. Birds were counted which were transit flying via the territory, as well as birds sitting on the lake water in the area of the observation point.Twenty‐one species of waterfowl have been registered. Analysis of long‐term dynamics has revealed a trend towards a decrease in the total number of migrating waterfowl. In the most abundant species, Anas acuta, this trend is statistically significant. In some species – Anas strepera and Cygnus Cygnus – the trend of dynamics is positive.Most likely reason for the decline in waterfowl numbers is excessive spring hunting. A reduced hunting duration or the introduction of a moratorium every few years may be among the responses required. We suggest using the period of mass migration to monitor the waterfowl resource. This period is shorter and when the greatest number of birds migrate.